Identifying complementary and alternative medicine recommendations for insomnia treatment and care: a systematic review and critical assessment of comprehensive clinical practice guidelines - Zhao, Fei-Yi; Xu, Peijie; Kennedy, Gerard A.; Conduit, Russell; Zhang, Wen-Jing; Wang, Yan-Mei; Fu, Qiang-Qiang; Zheng, Zhen (Frontiers in Public Health, 2023)
Background There is a need for evidence-informed guidance on the use of complementary and alternative medicine (CAM) for insomnia because of its widespread utilization and a lack of guidance on the balance of benefits and harms. This systematic review aimed to identify and summarise the CAM recommendations associated with insomnia treatment and care from existing comprehensive clinical practice guidelines (CPGs). Meanwhile, the quality of the eligible guidelines was appraised to assess the credibility of these recommendations. Methods Formally published CPGs incorporating CAM recommendations for insomnia management were searched for in seven databases from their inception to January 2023. The NCCIH website and six websites of international guideline developing institutions were also retrieved. The methodological and reporting quality of each included guideline was appraised using AGREE II instrument and RIGHT statement, respectively. Results Seventeen eligible GCPs were included, and 14 were judged to be of moderate to high methodological and reporting quality. The reporting rate of eligible CPGs ranged from 42.9% to 97.1%. Twenty-two CAM modalities were implicated, involving nutritional or natural products, physical CAM, psychological CAM, homeopathy, aromatherapy, and mindful movements. Recommendations for these modalities were mostly unclear, unambiguous, uncertain, or conflicting. Logically explained graded recommendations supporting the CAM use in the treatment and/or care of insomnia were scarce, with bibliotherapy, Tai Chi, Yoga, and auriculotherapy positively recommended based on little and weak evidence. The only consensus was that four phytotherapeutics including valerian, chamomile, kava, and aromatherapy were not recommended for insomnia management because of risk profile and/or very limited benefits. Conclusions Existing guidelines are generally limited in providing clear, evidence-informed recommendations for the use of CAM therapies for insomnia management due to a lack of high-quality evidence and multidisciplinary consultation in CPG development. More well-designed studies to provide reliable clinical evidence are therefore urgently needed. Allowing the engagement of a range of interdisciplinary stakeholders in future updates of CPGs is also warranted.